Misconceptions of Prospective Biology Teachers on Fructus Material Using the Certainty of Response Index Technique - Mar'atul Afidah; Sri Wahyuni (Journal of Natural Science and Integration, 2023)
This study is aimed to identify misconceptions about fructus that occur in biology teacher candidates. To achieve this goal, this study used a descriptive research method with a survey method to describe a condition of misconceptions of prospective biology teacher students based on the CRI technique. This research was carried out at the fkip of lancang kuning university in the 2020/2021 academic year. The population in the study were biology education students who contracted the plant morphology course with the research sample selected by saturated sampling or total sampling, amounting to 35 people. The data collection technique is by giving a fructus concept ability test in the form of multiple choice equipped with a cri scale with a total of 15 question numbers. Data analysis techniques were used using the cri (certainty of response index) technique and the levels of conception and constructive misconceptions were presented descriptively. The findings of the study were obtained from 525 conceptions that there were three categories of conceptions that occurred among prospective biology teacher students about fructus, namely understanding the concept of fructus 27.75% and not understanding the concept of fructus 37.35% and misconceptions 34.90%. Biology teacher candidate students were found to have misconceptions with moderate levels of misconceptions. The concept of misconception occurs in students about fructus, namely the concept of true fruit groups and pseudo fruit groups in fruits. It is hoped that the findings of misconceptions in prospective teachers can become the basis for parties to develop appropriate models or media to reduce the level of misconceptions.Keywords: misconceptions, fructus, CRI